2021
DOI: 10.1021/acs.biomac.1c00244
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Photothermally Targeted NIR-Responsive Nanomedicine-Induced Immunogenic Cell Death for Effective Triple Negative Breast Cancer Therapy

Abstract: Triple negative breast cancer (TNBC) is a breast cancer subtype. At present, TNBC patients do not have approved targeted therapy. Therefore, patients primarily depend on forceful systemic chemotherapy that has unavoidable harmful side effects, resulting in inadequate therapeutic outcomes and leading to a high mortality rate. Hence, there is an urgent need to develop targeted therapies for the TNBC populace. Developing a new nanotherapeutic approach of combinational therapy could be an effective alternative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…An excellent PAT is characterized by strong light absorption, strong photothermal conversion ability, stability, good biocompatibility, and the ability to turn off PTT in the non-treatment stage [92]. Near-infrared PAT include polyaniline [93], copper sulfides (CuS) NPs [94], as well as inorganic NPs, such as gold-based NPs [95]. Inorganic NPs show high photothermal conversion efficiency but relatively poor biocompatibility and toxicity [95], while liposome-based material and organic-conjugated polymers exhibit relatively better biocompatibility [96].…”
Section: Immunotherapy Combined With Pttmentioning
confidence: 99%
See 1 more Smart Citation
“…An excellent PAT is characterized by strong light absorption, strong photothermal conversion ability, stability, good biocompatibility, and the ability to turn off PTT in the non-treatment stage [92]. Near-infrared PAT include polyaniline [93], copper sulfides (CuS) NPs [94], as well as inorganic NPs, such as gold-based NPs [95]. Inorganic NPs show high photothermal conversion efficiency but relatively poor biocompatibility and toxicity [95], while liposome-based material and organic-conjugated polymers exhibit relatively better biocompatibility [96].…”
Section: Immunotherapy Combined With Pttmentioning
confidence: 99%
“…To specifically target CD44, Yasothamani et al [93] designed a conjugation of hyaluronan (HA)−polyaniline (PANi)−imiquimod (R837), denoted as HA-PANi/R837. The high photothermal conversion efficiency of PANi means that it has a significant thermal ablation effect in solid tumor.…”
Section: Immunotherapy Combined With Pttmentioning
confidence: 99%
“…These results demonstrated that photothermal cancer therapy combined with immunotherapy developed the anticancer killing effect. PANi NPs showed good biocompatibility so that after the PTT treatment no significant changes in mice body weight was observed in any of the groups, indicating that the toxicity of the treatment was not obvious 32 (Fig. 3c).…”
Section: Photothermal Ablation Of Tumor By Induced Icd-marker Releasementioning
confidence: 95%
“…Another report showed that the sudden burst CO 2 bubbles in the tumor microenvironment can also stimulate efficient immunogenicity by inducing membrane rupture of cancer cells ( Jeon et al, 2022 ). Several studies have demonstrated that PTT can not only directly destroy tumor cells but also indirectly stimulate systemic immunity ( Jiao et al, 2021 ; Yasothamani et al, 2021 ); therefore, the combined treatment using PTT and an ICD-inducer is anticipated to improve the efficiency of immunotherapy. Nevertheless, the hypoxic characteristics of tumors impair the efficiency of PTT and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%